Encouraging Local MSME Products Towards Global Through Blockchain Technology - Supriadi, Iman; Ida, Rahvita; Wardoyo, Dewie Tri Wijayati (Universitas Negeri Surabaya, 2024)
This study aims to analyze the role of blockchain technology in enhancing global market access for local MSME (Micro, Small, and Medium Enterprise) products, identify key barriers to its adoption, and formulate implementation strategies tailored to the needs and capacities of MSMEs. The research employs a qualitative case study approach based on a literature review. Data were obtained from academic journals, reports, and policy documents related to blockchain, MSMEs, and international trade. Analysis was conducted using content analysis methods, supplemented by source and theoretical triangulation to enhance the validity of the findings. Blockchain technology has proven capable of supporting MSME products in entering global markets through product traceability, supply chain efficiency, and cross-border payment systems. The challenges faced by MSMEs include low technological literacy, high implementation costs, and inadequate regulatory frameworks. Recommended implementation strategies include improving technological literacy, providing subsidies for blockchain adoption, and developing adaptive regulations. This study contributes by offering a strategic framework for MSMEs to adopt blockchain technology and serves as a reference for policymakers and business stakeholders in fostering an innovation ecosystem that supports the global competitiveness of MSMEs.